Urgensi Kebijakan IAIN Langsa Dalam Penggunaan Sistem Informasi Perkantoran Digital (SITOTAL) - Syamsul Bahri; M. Anzaikhan; Sari Damayanti; Rahmat (JAKA: Jurnal Analisis Kebijakan Kementerian Agama, 2022)
As an ideal institution, constructive and innovative policies are needed and can provide benefits for every element in it. Furthermore, a policy can be said to be effective if it can be implemented and solve various administrative problems. The COVID-19 pandemic that occurred in early 2019 to 2021 made various global administrative sectors paralyzed, including at IAIN Langsa. This fact makes it difficult for the academic community of IAIN Langsa to find it difficult to attend attendance, leave leave, report ranks and other administrative interests. Not to mention the existence of rules related to lockdown, social distancing, and work from home (WFH) urging the IAIN Langsa policy analyst team to take precise steps in responding to these dynamics. This article belongs to field research with a qualitative approach. The methodology used is a phenomenological study of the administrative policies of IAIN Langsa which eventually resulted in an application called Sitotal. The results of the study concluded; First, the presence of a digital office system (Sitotal) as a result of the policies of the leadership of IAIN Langsa is very urgent to implement an administrative system that was paralyzed due to the pandemic. Second, Sitotal gave IAIN Langsa its own color by creating a unique product and the only one on campus in Indonesia.